Female SUPELTAS’ Masculinity in Malang - Sawitri, Sri Endah; Fatmawati (Salasika, 2023)
This study aims to (1) find out the form of masculinity in women's SUPELTAS in the city of Malang, (2) find out the factors that influence masculinity in women's SUPELTAS in Malang city. This research uses descriptive qualitative approach. Sources of data used are data from interviews and documentation obtained by researchers. Data collection techniques used by researchers namely observation techniques, interviews and and documentation. Data analysis used by researchers is Miles Huberman's data analysis in the form of data reduction, data presentation and conclusion. The results of this study are (1) there are 2 forms of masculinity in SUPELTAS women in the city of Malang, namely masculine personality in the form of being assertive and wise, independent, brave and loud and masculine in appearance in the form of short hair, wearing a hat and wearing pants. (2) Factors that influence masculinity in women's SUPELTAS in Malang city are the SUPELTAS regulations that have been stipulated and forced to live on the streets.